Alcohol consumption and sickness absence: Evidence from panel data - Edvard Johansson; Petri Böckerman; Antti Uutela (The Research Institute of the Finnish Economy (ETLA), 2007)
– Objective : This paper examines the relationship between alcohol consumption and sickness absence. Methods : We use regional panel data from Finland over the period 1993-2005. The data on individuals' health that we are using originates from Health Behaviour and Health among the Finnish Population conducted by the National Public Health Institute. To control for the effect of economic conditions on the prevalence of sickness absence, we aggregate Health Behaviour and Health among the Finnish Population to the regional level. Then we link the data, using information on individuals' residence, to the regional statistics produced by Statistics Finland. Panel data allows us to control for unobserved determinants of lifestyle behaviours associated with the region and survey year. Results : The results show that alcohol consumption is associated with sickness absence, and particularly so for men. Therefore, the earlier aggregate time-series evidence from Sweden is largely confirmed in a regional panel data setting. Conclusion : It is important to take into account the effects of alcohol consumption on sickness absence when considering the appropriate level of taxation of wines and spirits in Nordic countries.
Keywords: I10; 330; Alcohol consumption; sickness absence; Alkoholkonsum; Krankheit; Fehlzeit; Panel; Finnland